Managing Workforce 2000: Gaining The Diversity Advantage - Thornicroft, Kenneth Wm. (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Managing Workforce 2000: Gaining The Diversity Advantage," by David Jamieson and Julie O'Mara.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z